BEBERAPA SIFAT MINYAK SABAL-SABAL (CINNAMOMUM SUBAVENIUM) (Some properties of Sabal-sabal (Cinnamomum subavenium) oil - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The physico-chemical properties and identification of new essential oils from Cinnamomum subavenium Miq (Sabal-sabal) bark prepared by using vacum destillation process is presented in this paper. The bark used was subjected to three different position i e : top, middle and bottom. The physico-chemical properties observed are specific gravity, acid value, ester conent, solubility in ethanol 80 % refractive index at 20°C, and optical rotation. The major components of essential. oils were identified by using peak enrichment technique and retention data from essential oil standart of the Gas Liquid Chromatographic method. In addition, the-yield was determined.The result shows that the yield ranges from 1. 73 - 1. 87 % specific gravity at 25°C from 0. 93689 - 0. 94454, refractive index at 20°C from 1.47966- 1.48542, optical rotation at 25°C from -11°9' to -12°39', acid value from 1,02 – 1.34, ester content from 6.45 - 8.29 and solubility in ethanol 80 % is soluble in 1:1. The composition of major components of the Sabal-sabal oil were iso borneol ranges from 17.75 - 22.15 %, aldehyde C-II from 6.09-17.ll %, cineol from 13.20- 14.23 %, iso bornyl acetate from 5.28 -8.47 %, a terpinyl acetale from 5.21 - 8.81 %. Furthermore some components found in the oil were a pinen, β pinen, terpinene , β caryophyllene, aldehyde C-9, cinamaldehyde and hidroxy citronellol Based on major components and its derivatives the oil is used in the perfumery and flavor industry.